Retrospective study of atypical presentation in cases diagnosed as acute myocardial infarction - Elkandow, Ali Elhaj Mohammed (2015)

(untitled)
Introduction: AMI presentation is consider fundamental part for diagnosis as a history of chest pain usually lead the ED physicians to think about it or at least he/she is considered as one of differential diagnosis from all life threatening conditions in thorax region. In many patients, physician might face a challenge or may depend on his experience or technology to figure out the cause of illness if the patient came without chest pain although he/she finally diagnosed as AMI. Objectives: In this study we have determined the prevalence of AMI in KB in north Malaysian. In addition to that this study focused on three main atypical presentations which include atypical chest pain, shortness of breathing and epigastric pain. Others objectives include the outcome of each clinical presentations as well as clinical approached in ED or medical ward. Furthermore, the study compared the duration of admission for all typical and atypical presentations mentioned above. One of the objectives of this study it assessed and correlated the common risk factors in term of comorbidities which might affect the initial AMI presentation. Methodology: The study design was a retrospective study of patients presenting for treatment in Hospital Universiti Sains Malaysia from January 1, 2011, to December 31, 2012. This study non experimental research design using data collected from patient’s files of folders. Data collection for this study took place during eight weeks period from June 1, 2013, through August 1, 2013. Total of 442 patients with confirmed as AMI enrolled from 1st of January 2011 to 31st of December 2012 in HUSM. Data was analyzed by using SPSS version 22. Main Outcome Measures: Prevalence of atypical AMI presentation include; atypical chest pain, SOB, epigastric pain and others, Mortality rate and how patients were approached in compare to those came with classical chest pain. Results: Results from data of AMI patients were noticed atypical presentation more common, than typical chest pain (58.6% vs. 41.4%). Mean age of AMI with typical chest pain was found younger than AMI with less chest pain or those without chest pain (58.57 vs. 63.12 years). Time to perform ECG, or started management also was influenced by initial presentation this was appear faster e.g. in DOOR to ECG; in typical presentation 10 minutes, while in atypical presentation the mean time was 37.27 minutes. Also the duration of admission was found to be longer in AMI with atypical presentation (5 vs. 6 days). The mortality rate was higher in atypical presentation when it compared with typical chest pain (9.7% vs. 2.5%). Conclusions: Our results data were shown AMI without classical presentations were common and patients at risk to be delayed in term of approach as well as management. Patients were treated less aggressively in atypical presentation; also they could be delayed or stayed longer in ED before admission. Moreover, usually they carry poor prognosis and high mortality rate.